Does the Degree of Perihepatitis Have Any Relevance to the Severity of the Manifestations of Pelvic Inflammatory Disease on Multidetector Computed Tomography?. Issue 6 (November 2015) - Kim, Ji Su; Kim, Hyun Cheol; Kim, Sang Won; Yang, Dal Mo; Rhee, Sun Jung; Shin, Jong Soo
Abstract : Purpose: This study aimed to evaluate the relationship between the degree of perihepatitis and the severity of pelvic inflammatory disease (PID) on multidetector computed tomography (MDCT). Methods: A total of 177 women with PID who underwent biphasic abdominal computed tomography (CT) scans were enrolled. Two reviewers retrospectively reviewed the CT scans with consensus and subjectively categorized the severity of PID into 4 grades (normal, mild, moderate, and severe). Another reviewer independently assigned the extent (grades 0 to 4) and the depth (grades 0 to 4) of hepatic surface enhancement in terms of the degree of perihepatitis. Relationships between the degree of perihepatitis and the CT severity as well as each CT manifestation of PID were evaluated using the χ 2 test or a cumulative logistic regression analysis. Results: Of the 177 patients, 99 (55.9%) showed hepatic surface enhancement. The severity of PID on MDCT was significantly related with the degree of perihepatitis (all P < 0.001). Salpingitis, oophoritis, pelvic fat haziness, complicated ascites, and omental/mesenteric fat infiltration were significantly related with the degree of perihepatitis (all P < 0.05). Among these variables, omental/mesenteric fat infiltration (odds ratio = 10.9) and salpingitis (odds ratio = 6.0) were the CT manifestations that were most associated with the presence of perihepatitis in PID. Conclusions: The degree of perihepatitis seems to show a relationship with the severity of PID on MDCT. Omental/mesenteric fat infiltration and salpingitis can be strongly related with perihepatitis in PID.